2008
DOI: 10.1007/s00411-008-0199-3
|View full text |Cite
|
Sign up to set email alerts
|

Does single-dose cell resistance to the radio-mimetic zeocin correlate with a zeocin-induced adaptive response in Chlamydomonas reinhardtii strains?

Abstract: This study aimed to test whether a correlation exists between single-dose resistance to zeocin and the ability to develop a zeocin-induced adaptive response (AR) in Chlamydomonas reinhardtii strains. Three genotypes were used: wild type (WT) strain 137C and two strains (H-3 and AK-9-9), which are highly resistant to radiation based on survival studies. Based on a micro-colony assay, the strains could be arranged according to their single-dose resistance to zeocin as follows: AK-9-9 > H-3 > 137C. However, zeoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Despite abundant literature available on the action of bleomycin [ 16 , 17 ], studies on the effect of Zeo have been focused on Zeo as causing transformants in various test-systems [ 18 , 19 , 20 ]. Data on the DNA-damaging action of Zeo in only one plant system has been reported [ 13 , 14 ]. Therefore the second step of this study was to evaluate DNA-damaging (genotoxic) potential of Zeo over a wider concentration range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite abundant literature available on the action of bleomycin [ 16 , 17 ], studies on the effect of Zeo have been focused on Zeo as causing transformants in various test-systems [ 18 , 19 , 20 ]. Data on the DNA-damaging action of Zeo in only one plant system has been reported [ 13 , 14 ]. Therefore the second step of this study was to evaluate DNA-damaging (genotoxic) potential of Zeo over a wider concentration range.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of zeocin (Zeo) on the DNA are detrimental for cells. Zeo, as a member of bleomycin/phleomycin family of glycopeptide antibiotics, is known to bind to DNA and induce oxidative stress in different organisms, like ionizing radiation, producing predominantly single and double strand breaks (SSBs/DSBs), as well as base losses [ 13 , 14 ]. Many defense mechanisms have been evolved to minimalize such effects of oxidative stress, including the AR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiomimetic zeocin (Zeo) (Cas No. : 11006-33-0, Invi-troGen), which belongs to the bleomycin family of antibiotics, was used as a standard mutagenic factor, well investigated and described in our previous studies (Chankova et al, 2007;Dimova et al, 2009;Kopaskova et al, 2012).…”
Section: Standard Mutagenmentioning
confidence: 99%
“…Growing evidences have shown that the cell responses to ionizing radiation through genes associated with DNA repair, stress response, cell cycle control and apoptosis. TP-53 plays important roles in control of the low-dose radioadaptive response [ 2 , 6 , 7 ]. The microarray analysis performed by Lanza et al has shown that 111 genes are modulated at different doses of irradiation.…”
Section: Introductionmentioning
confidence: 99%